Dampak Pemberian Bantuan Modal terhadap Pendapatan Pengusaha Kecil Sektor Perdagangan di Kota Waisai Kabupaten Raja Ampat - , Henokh Suruan, S.E.; , Prof. Dr. Catur Sugiyanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Economic development aims at improving community welfare particularly small and medium entreprises (SMEs). One of the ways of empowering the actors of SME is to provide them with capital aid in order that they can increase income after the aid given. In Raja Ampat Regency, actors of the SME cannot develop well because of the limited capital aid. The program of capital aid for the small businessâ actors has been carried out and to date no academic study is conducted. Therefore, purpose of the study is to analyze the effect of the capital aid on the income of small businessâ actors. The study was conducted by using a quantitative method. Data used were primary data obtained by using questionnaire and interview, and secondary data obtained by using a documentation technique. The data collected were analyzed by using the t-test method. Result of the study shows that three hypotheses were accepted (or H0 was rejected), i.e. second hypothesis (education is junior high schoolâJHS), fifth hypotesis (age is above 40 years) and ninth hypotesis (non-indigenous), because tcalculation was higher than t-table, and the increase of average income was higher after the capital aid. The increase of average income among the actors of the SME with JHS was IDR1,298,235 compared with those with elementary school (ES) (IDR879,286) and senior high school (SHS) (616,667)